Assessment of early toxicity and response in patients treated with proton and carbon ion therapy at the Heidelberg Ion Therapy Center using the raster scanning technique - Rieken, Stefan; Habermehl, Daniel; Nikoghosyan, Anna; Jensen, Alexandra; Haberer, Thomas; Jäkel, Oliver; Münter, Marc; Welzel, Thomas; Debus, Jürgen; Combs, Stephanie (International journal of radiation oncology, biology, physics, 2011)
Puropose - To asses early toxicity and response in 118 patients treated with scanned ion beams to validate the safety of intensity-controlled raster scanning at the Heidelberg Ion Therapy Center. - Patients and Methods - Between November 2009 and June 2010, we treated 118 patients with proton and carbon ion radiotherapy (RT) using active beam delivery. The main indications included skull base chordomas and chondrosarcomas, salivary gland tumors, and gliomas. We evaluated early toxicity within 6 weeks after RT and the initial clinical and radiologic response for quality assurance in our new facility. - Results - In all 118 patients, few side effects were observed, in particular, no high numbers of severe acute toxicity were found. In general, the patients treated with particle therapy alone showed only a few single side effects, mainly Radiation Therapy Oncology Group/Common Terminology Criteria grade 1. The most frequent side effects and cumulative incidence of single side effects were observed in the head-and-neck patients treated with particle therapy as a boost and photon intensity-modulated RT. The toxicities included common radiation-attributed reactions known from photon RT, including mucositis, dysphagia, and skin erythema. The most predominant imaging responses were observed in patients with high-grade gliomas and those with salivary gland tumors. For skull base tumors, imaging showed a stable tumor outline in most patients. Thirteen patients showed improvement of pre-existing clinical symptoms. - Conclusions - Side effects related to particle treatment were rare, and the overall tolerability of the treatment was shown. The initial response was promising. The data have confirmed the safe delivery of carbon ions and protons at the newly opened Heidelberg facility.
Gesehen am 16.09.2022